2005
DOI: 10.1177/088840640502800107
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Traditional and Online Instruction in an Introduction to Special Education Course

Abstract: There has been a proliferation of college courses and programs offered via distance education and particularly via the Internet (online). Although there is evidence that distance education using video conferencing or off-campus classes is effective, there is insufficient research addressing the online classes. Much of the existing research has investigated perceptions rather than outcomes. In contrast, this research presents a comparison of performance of candidates in introductory special education classes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…For example, researchers cite that dropout rates can be as much as 10–20% higher in online courses than in comparable face-to-face courses (Harris and Parrish, 2006; Xu and Jaggars, 2013). Still other researchers report no difference between academic outcomes in face-to-face and online learning environments (e.g., Bernard et al, 2004; Steinweg et al, 2005; Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…For example, researchers cite that dropout rates can be as much as 10–20% higher in online courses than in comparable face-to-face courses (Harris and Parrish, 2006; Xu and Jaggars, 2013). Still other researchers report no difference between academic outcomes in face-to-face and online learning environments (e.g., Bernard et al, 2004; Steinweg et al, 2005; Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…The notion of equivalency relates to the fact that distance education and traditional university instruction should reflect the same level of academic rigor and produce similar student outcomes. However, like Steinweg et al (2005) and Tiffin and Rajasingham (1995), we found little evidence that researchers have sought to compare and contrast the efficacy of distance versus traditional face-to-face instruction. Most of what we found was related to consumer satisfaction data rather than more rigorous evaluation efforts.…”
Section: Interaction and Communicationmentioning
confidence: 80%
“…Chính vì vậy, việc giảng dạy lấy người học làm trung tâm đòi hỏi nhiều hơn là chỉ đơn giản học cách sử dụng công nghệ; đồng thời cũng đòi hỏi người dạy phải học những cách dạy mới và khác nhau để thu hút học sinh vào môi trường học tập ảo (DeNigris & Witchel, 2000; Kearsley, 2000) [4,5]. Đánh giá hiệu quả học tập trực tuyến của Steinweg, Davis và Thomson (2005) [6] đã cho thấy không có sự khác biệt đáng kể về mặt thống kê trong những thay đổi về kiến thức, cách xử lý và hiệu suất của người học đăng ký tham gia môi trường học tập trực tuyến và truyền thống trong một khóa học giáo dục đặc biệt. Jonassen, (1994) khi kiểm tra cách sử dụng công nghệ trong lớp học trực tuyến trong khuôn khổ kiến tạo đã nhấn mạnh vai trò của người hướng dẫn [7].…”
Section: Mở đầU *unclassified